(untitled) (Historia Agraria de América Latina, 2025)
This paper shows how the animal resources of the Orinoco played a decisive role in the military success of the Venezuelan and Colombian Independentistas between 1818 and 1821. It first analyzes the constitution of new agricultural activities in the Orinoco from the 18th century onwards, mainly cattle raising, essentially through the work of religious orders. Then it is demonstrated that, through international trade, the resources of the Orinoco were exported mainly to the Caribbean, where mules and cattle were indispensable for the mills (and also for feeding, in the case of cattle). Thus, this work aims to demonstrate that commerce between the cattle commodity frontier of the Orinoco and the consolidated and the sugar commodity frontier of the Caribbean enabled the patriot army of Venezuela and Colombia to defeat the Spanish forces.